An Analysis of Student’s need on English Accounting Materials at Universitas Muhammadiyah Makassar - Sujariati; Yassir Mallapiang; satang, Satang (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
This research focuses on to find out the student’s needs of the learning English accounting materials as accounting study program, and absolutely it will be contributed to develop syllabus of English accounting study program. The method of this study is mix-methods with quantitative and qualitative design. The subject of the research are the students in accounting Muhammadiyah University of Makassar. The instrument in this research are questionnaire and interview. A questionnaires and interview were constructed to find out the student’s perception of existing materials, the weaknesses, the need, and wants of the students to which a good and appropriate English book of Accounting. The findings showed that the students of accounting program need a specific material in term particular topics of accounting activity which has tight relationship with their study program. Other findings showed the students’ wants about clearly structures of materials in term input, Specific topic materials, language use, procedure, setting classes’ instruction, and feedback which are provided all on the course book. All findings would be contributed on a course book as the students’ guider in learning English.